Sistematização de projetos de controladores fuzzy através de programação orientada a objetos - LEITÃO, Álvaro Luís dos Reis (Universidade Federal do Pará, 2013)
By using object oriented language programming and, applying a specific programming technique, it‟s possible to generate a set of generic classes whose objects represent each block of a fuzzy controller as well its linguistic variables. Such classes, being applied in a systematic way, make easy the programming of a set of controllers of this nature. This work presents this technique and shows the results obtained via a model simulation of a inverted rotational pendulum which is controlled by a control system composed by three fuzzy controllers designed and built under this point of view.